Memorial dedicated to Lieutenant Colonel John Campbell - Ghosh, Ayan (2023)
Memorial erected by the East India Company in memory of Lieutenant Colonel John Campbell, who bravely defended Mangalore for eight months when it was laid siege by the Kingdom of Mysore (supported by the French) during the Second Anglo-Mysore War (1780-1784). Campbell survived the siege but died from hardship at the age of 33. His memorial was made by British sculptor Charles Peart (1759–1798) in London, engraved on the pedestal (below the lion faces).